Infraesphinteric fundoesophagostomy. (Biondi-king-Ferrari procedure). - Badano Repetto, José L (Cirugía del Uruguay, 1983)
The author presents bis experienc,a with seven megaesophagus treated with the Biondi-KingFerrari procedure.